The model estimates the level of efficiency of corporate governance - N. A. Volkova (Статистика и экономика)
The majority of Russian enterprises have problems with updating their production assets and therefore are in dire need of  investments. A huge role in the investment attractiveness of  enterprises is provided by its corporate governance system. The lack of a well-developed stock market in Russia is not the last problem  pushing investors away. The purpose of this work is to develop a  mathematical model for assessing the effectiveness of corporate  governance of the enterprise to make a decision on foreign  investment in the oil industry corporation. In the sources available  for analysis, insufficient attention is paid to the analysis and  development of methods for assessing the effectiveness of corporate governance when deciding on the external investment of the  corporation. In order to make a decision of a potential investor to  invest in a company, the investor must have an idea of the activities  of the company and its economic and financial indicators. The  system of performance indicators of the corporation’s personnel, which affect its value, has a poorly structured structure.  To solve the problems of weakly structured systems it is necessary  to use fuzzy logic methods. These methods allow making qualitative  assessment of activity of the enterprise and its administrative  personnel, giving the chance to define level of management of the  enterprise and quality of performers of work. Existing models of  corporate governance performance assessment borrowed from  abroad are not effective in Russia. The level of corporate governance in the company is determined using ratings from the major rating  agencies such as S&P, RBC, EXPERT RA, CORE rating. But for this  method of measurement, there is one important condition: the estimated company must be included in the lists of these  agencies in order to monitor and analyze its corporate governance.  However, often in Russia, not all companies are included in the list of rating agencies, especially if these companies belong to medium- sized businesses. In the paper the model of corporate governance  efficiency evaluation is presented in the form of a system of  components, each of which is formed from economic indicators,  taking into account both the economic characteristics of the  enterprise and the qualitative composition of its personnel and not  tied to the quotes of the company’s shares in the stock markets. This model is built with the help of the method of fuzzy logic, which  allows combining quantitative and qualitative indicators. Using the  theory of fuzzy sets, the difference in the values of the initial  indicators is eliminated when assessing the level of efficiency of  corporate governance, and through operations on linguistic variables, the core component of the corporate governance level is combined. With the help of productive rules of fuzzy logic, the  numerical components of the level of efficiency of corporate  governance are given to fuzzy form. The developed model of  decision-making of a potential investor about investing in an  enterprise, based on the calculation of the assessment of the level of efficiency of its corporate governance, shows the potential investor  the level of economic and financial management of the enterprise,  the quality of management and working staff of the enterprise,  promotes the decision on the feasibility of investing in corporations.